Effect of specimen geometry, quenching and trigger mechanism on crushing performance of single hat column - Izzah, A. R. N.; Salwani, Mohd Salleh; Tan, S. W.; Mas Ayu, Hassan; R., Daud (IOP Publishing, 2019)
Paraffin deposition in the crude oil production pipeline has been an alarming problem to the flow assurance community. This phenomenon causes a tremendous amount of material loss in the production and substantial resources are expended to resolve these flow assurance problems—which included the chemical treatment. This study examined an agricultural non-ionic silane-based surfactant and its blends (with silica nanoparticles) as a flow improver using Malaysian light crude oil (42.4°API). In particular, this study performed the following experimental measurements: wax appearance temperature, pour point, viscosity, and FTIR spectroscopic analysis. The result showed that the surfactant-nanoparticles blend affected the viscosity (significant reduction by approximately 67 %) within certain temperature range and were able to depress both pour point (to 4°C) and wax appearance temperature (15.6°C). It was also revealed that the most potent blend consisted 400 ppm of silane-based surfactant and 200 ppm of SiO2 nanoparticles. The study also evaluated the underlying mechanisms for the variation of viscosity through FTIR spectroscopic analysis.